2017
DOI: 10.1007/978-3-319-51963-0_19
|View full text |Cite
|
Sign up to set email alerts
|

Exact Quantum Query Complexity of $$\text {EXACT}_{k,l}^n$$

Abstract: In the decision tree model, one's task is to compute a boolean function f : {0, 1} n → {0, 1} on an input x ∈ {0, 1} n that is accessible via queries to a black box (the black box hides the bits xi). In the quantum case, classical queries and computation are replaced by unitary transformations. A quantum algorithm is exact if it always outputs the correct value of f (in contrast to the standard model of quantum algorithms where the algorithm is allowed to be incorrect with a small probability). The minimum num… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Ambainis, Iraids and Smotrovs [AIS13] showed a tight bound on the exact quantum query complexity of EXACT k (the Boolean function that outputs 1 iff the Hamming weight of the input equals k) for all k, and TH k (the Boolean threshold function that outputs 1 iff the Hamming weight of the input is at least k) for all k. Ambainis, Gruska and Zheng [AGZ15] showed that a function on n input variables has exact quantum query complexity n iff it is equal to AND n up to negations and permutations of the input variables and negation of the output. More recently, Ambainis, Iraids and Nagaj [AIN17] showed a tight bound for the exact quantum query complexity of EXACT k,ℓ (the Boolean function that outputs 1 iff the Hamming weight of the input equals k or ℓ) for all k, ℓ.…”
Section: Introductionmentioning
confidence: 99%
“…Ambainis, Iraids and Smotrovs [AIS13] showed a tight bound on the exact quantum query complexity of EXACT k (the Boolean function that outputs 1 iff the Hamming weight of the input equals k) for all k, and TH k (the Boolean threshold function that outputs 1 iff the Hamming weight of the input is at least k) for all k. Ambainis, Gruska and Zheng [AGZ15] showed that a function on n input variables has exact quantum query complexity n iff it is equal to AND n up to negations and permutations of the input variables and negation of the output. More recently, Ambainis, Iraids and Nagaj [AIN17] showed a tight bound for the exact quantum query complexity of EXACT k,ℓ (the Boolean function that outputs 1 iff the Hamming weight of the input equals k or ℓ) for all k, ℓ.…”
Section: Introductionmentioning
confidence: 99%
“…The exact quantum query complexity for partial functions was dealt with also in [10,15] and for total functions in [5][6][7]28].…”
Section: Exact Query Complexitymentioning
confidence: 99%
“…The exact quantum query complexity for partial functions was dealt with also in Brassard and Høyer (1997) and Deutsch and Jozsa (1992) and for total functions in Ambainis (2013), Ambainis et al (2013Ambainis et al ( , 2015 and Montanaro et al (2015).…”
Section: Exact Query Complexitymentioning
confidence: 99%
“…For a function f , quantum advantage can be investigated by comparing the exact quantum query complexity and the deterministic decision tree complexity [ 1 ], where denotes the minimum number of queries used by any classical deterministic algorithm. Over the past decade, there have been many results on the quantum query model [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. In particular, Ambainis et al [ 14 ] proved that exact quantum algorithms have advantage for almost all Boolean functions in 2015.…”
Section: Introductionmentioning
confidence: 99%